Mapuche Worldview, Territory, and Language: Narratives of Mapuche Speakers and Elders - Fabiola Maldonado García; Susan Sanhueza Henríquez; Carolina Aroca Toloza (Societies, 2024)
This article addresses the relationship between worldview, territory, and language among the Mapuche people. Our research aims to explore, through the voices of Mapuche elders, the sociocultural, political, and territorial knowledge that guides the teaching and transmission of Mapuzugun to new generations. In alignment with the proposed objective, we have adopted a socio-critical approach to explore Mapuche identity through the territorial and communal dimensions that underpin linguistic revitalization. The findings reveal that the elders possess a vast source of knowledge, serving as primary cultural bearers through epistemology centered on the unity of language and territory.